2012
DOI: 10.2741/e358
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal endometriosis is an inflammatory disease

Abstract: Introduction 2.1. Peritoneal fluid and environment in peritoneal endometriosis 2.2. Oxidative stress and peritoneal endometriosis 3. Involvement of iron in the pathogenesis of peritoneal endometriosis 3.1. Iron overload in the peritoneal cavity of endometriosis patients 3.2. Origin of iron in the pelvic cavity 3.3. Iron metabolism in the pelvic cavity 3.4. Effect of iron overload on endometriosis development 3.5. Iron chelators as endometriosis treatment 4. Involvement of nuclear factor-kappa B in the pathogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(14 citation statements)
references
References 122 publications
(206 reference statements)
0
12
0
2
Order By: Relevance
“…The central role in endometriosis belongs to local inflammation, which triggers the development of the disease and induces pain and infertility [21]. In support of this statement, a wide range of studies reported that the peritoneal fluid of endometriotic patients contained high levels of macrophages and immune cells, which secrete cytokines, angiogenic factors, and growth factors [22].…”
Section: Endometriosis-an Inflammatory Diseasementioning
confidence: 98%
See 1 more Smart Citation
“…The central role in endometriosis belongs to local inflammation, which triggers the development of the disease and induces pain and infertility [21]. In support of this statement, a wide range of studies reported that the peritoneal fluid of endometriotic patients contained high levels of macrophages and immune cells, which secrete cytokines, angiogenic factors, and growth factors [22].…”
Section: Endometriosis-an Inflammatory Diseasementioning
confidence: 98%
“…Alternatively, in vivo, the integrative activation of NF-kappa B subunits has been highlighted in ectopic areas of endometrial tissue [34]. The researcher's common point of view is that in endometriosis, NF-kappa B activated macrophages release IL-1, 6, 8, COX-2, TNF-alpha, and vascular endothelial growth factor (VEGF); thus, perpetuating the inflammatory pathway [21].…”
Section: Endometriosis-an Inflammatory Diseasementioning
confidence: 99%
“…ROS production enhances NF-κB in peritoneal macrophages leading to cell growth, angiogenesis and inflammation in endometriosis cells [44].…”
Section: Introductionmentioning
confidence: 99%
“…It is now well established that chronic inflammatory milieu in the peritoneal cavity of endometriosis patients contributes to pain and infertility associated with the disease 3 . Despite decades of research, current treatment option transiently alleviate but do not cure the disease.…”
Section: Introductionmentioning
confidence: 99%